Evolution of Physical Status From Diagnosis to the End of First-Line Treatment in Breast, Lung, and Colorectal Cancer Patients: The PROTECT-01 Cohort Study Protocol - Mallard, Joris; Hucteau, Elyse; Schott, Roland; Petit, Thierry; Demarchi, Martin; Belletier, Christine; Ben Abdelghani, Meher; Carinato, Hélène; Chiappa, Pascale; Fischbach, Cathie; Kalish-Weindling, Michal; Bousinière, Audren; et al. (Frontiers in Oncology, 2020)
Background. Cancer cachexia and exacerbated fatigue represent two hallmarks in cancer patients, negatively impacting their exercise tolerance and ultimately their quality of life. However, the characterization of patients’ physical status and exercise tolerance and, most importantly, their evolution throughout cancer treatment may represent the first step in efficiently counteracting their development with prescribed and tailored exercise training. In this context, the aim of the PROTECT-01 study will be to investigate the evolution of physical status, from diagnosis to the end of first-line treatment, of patients with one of the three most common cancers (i.e. lung, breast, and colorectal). Methods. The PROTECT-01 cohort study will include 300 patients equally divided between lung, breast and colorectal cancer. Patients will perform a series of assessments at three visits throughout the treatment: 1) between the date of diagnosis and the start of treatment, 2) 8 weeks after the start of treatment, and 3) after the completion of first-line treatment or at the 6-month mark, whichever occurs first. For each of the three visits, subjective and objective fatigue, maximal voluntary force, body composition, cachexia, physical activity level, quality of life, respiratory function, overall physical performance and exercise tolerance will be assessed. Discussion. The present study is aimed at identifying the nature and severity of maladaptation related to exercise intolerance in the three most common cancers. Therefore, our results should contribute to the delineation of the needs of each group of patients and to the determination of the most valuable exercise interventions in order to counteract these maladaptations. This descriptive and comprehensive approach is a prerequisite in order to elaborate, through future interventional research projects, tailored exercise strategies to counteract specific symptoms that are potentially cancer-type dependent and, in fine, to improve the health and quality of life of cancer patients. Moreover, our concomitant focus on fatigue and cachexia will provide insightful information about two factors that may have substantial interaction but require further investigation. Ethics and Dissemination This prospective study has been approved by the national ethics committee (2019-A00848-49) and all subjects will provide written informed consent in accordance with the Declaration of Helsinki.